Modeling the winter‐spring transition of first‐year ice in the western Weddell Sea. Issue 9 (11th September 2014) - Jeffery, N.; Hunke, E. C.
Abstract A new halodynamic scheme is coupled with the Los Alamos sea ice model to simulate western Weddell Sea ice during the winter‐spring transition. One‐dimensional temperature and salinity profiles are consistent with the warming and melt stages exhibited in first‐year ice cores from the 2004 Ice Station POLarstern (ISPOL) expedition. Results are highly sensitive to snowfall. Simulations which use reanalysis precipitation data do not retain a snow cover beyond mid‐December, and the warming transition occurs too rapidly. Model performance is greatly improved by prescribing a snowfall rate based on reported snow thicknesses. During ice growth prior to ISPOL, simulations indicate a period of thick snow and upper ice salinity enrichment. Gravity drainage model parameters impact the simulation immediately, while effects from the flushing parameter (snow porosity at the ice top) appear as the freeboard becomes negative. Simulations using a snow porosity of 0.3, consistent with that of wet snow, agree with salinity observations. The model does not include lateral sources of sea‐water flooding, but vertical transport processes account for the high upper‐ice salinities observed in ice cores at the start of the expedition. As the ice warms, a fresh upper‐ice layer forms, and the high salinity layer migrates downward. This pattern is consistent with the early spring development stages of high‐porosity layers observed in Antarctic sea ice that are associated with rich biological production. Future extensions of the model may be valuable in Antarctic ice‐biogeochemical applications.